Adnexal Torsion in Pediatric Age: Does Bolli's Score Work? Report of Two Cases. (8th December 2019) - Giambanco, L.; Iannone, V.; Borriello, M.; Scibilia, G.; Sozzi, G.; Chiantera, V.; Scollo, P.
Abstract : Adnexal torsion is a surgical emergency requiring early diagnosis in order to avoid demolitive surgery. Adnexal torsion's diagnosis could be very difficult in pediatric patients because children cannot explain symptoms accurately. Furthermore reproductive organs lie high in abdomen, causing unclear examinations findings. For reducing diagnostic mistakes or delay clinical and hematological criteria could be useful. No radiological criteria (CT or MRI) should be taken in count because of the costs and the required time. By combining clinical presentation in patients with OT three useful diagnostic variables have been identified: age, duration of pain, vomiting. Presence of vomiting, short duration of abdominal pain and high CRP levels have great predictive value for the diagnosis of adnexal torsion. In those patients an exploratory laparoscopy should be performed without any doubt and/or delay. These data may aid physicians in the evaluation of abdominal pain in premenarchal girls.